Implementasi Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan Pusat dan Daerah terhadap Pengendalian Belanja Pegawai Kabupaten dan Kota Se Sumatera Barat - Hamdani Hamdani; Zaenudin Zaenudin (Jurnal Eksplorasi Akuntansi, 2023)
One of the hot issues regulated in Law Number 1 of 2022 Concerning Financial Relations between the Central Government and Regional Governments (UU HKPD) is the limitation of regional employee spending outside of teacher allowances allocated through Transfers to Regions (TKD) of a maximum of 30% of budget spending. The HKPD Law provides for a transitional deadline of the next five years for the maximum employee spending obligations to be met. This condition is faced by West Sumatra Province which has 12 regencies and 7 cities. The portion of personnel expenditure to total APBD spending in 2019 was 38%, in 2020 it was 43%, soaring in 2021 to 40%. The interesting research questions are what are the factors that trigger the trend of increasing the share of personnel spending to APBD spending, can district and city governments in West Sumatra be able to fulfill the obligation to share personnel spending to APBD spending at a maximum of 30% in the next five years and what strategic policies should be done. The results of the study show that the portion of personnel expenditure to total APBD expenditure in the next five years is projected to be unable to meet the maximum percentage of personnel expenditure to total expenditure. Research data shows that the average portion of personnel spending to district/city regional spending is 43% in 2023, 44% in 2024, 46% in 2025, 48% in 2026, and 49% in 2027. For this reason, efforts are needed to reduce the portion of personnel expenditure to total regional expenditure which can be carried out with two strategies at once, namely not increasing the component of personnel expenditure, the amount of which is under the authority of the center and not adding employee formations within a certain period of time.